A Review of Ochratoxin A Occurrence, Condition for the Formation and Analytical Methods - Salasib Atumo (International Journal of Agricultural Science and Food Technology - Peertechz Publications, 2020)
Ochratoxin A (OTA) is a mycotoxin produced by several fungal species including Aspergillus ochraceus, A. carbonarius, A. niger and Penicillium verrucosum. Various studies report shown that Ochratoxin A can be leads several health problems for both animal and human health through the consumption of Ochratoxin A contaminated plant and animal origin foods. For instance, Ochratoxin A has been shown to be nephrotoxic, teratogenic, immunotoxic, and carcinogenic in human health. Therefore, the main aim of this review focused on the occurrence, analytical methods and the condition for the formation of Ochratoxin A. Number of studies finding report indicate that Ochratoxin A was existed in several processed and unprocessed food stuffs, species and different alcoholic beverage. Primarily, cereals and cereals contained food products have highly vulnerable for Ochratoxin A due the presence of high moisture contents. On the other hand, several environmental conditions are playing an important for the formation of Ochratoxin A in different food stuffs. For example, most important abiotic factors which influence the growth and Ochratoxin A production by such Spoilage fungi include water availability, temperature and gas composition. Finally, several analytical methods are used for detection of Ochratoxin A from different plant and animal origin foods such as Thin layer chromatography, Enzyme linked immunosorbent assay and High performance liquid chromatography. However, based on the sensitivity, resolution and efficiency currently high performance liquid chromatography techniques are more popular and advanced analytical techniques for different mycotoxins groups particularly, Ochratoxin A and Aflatoxins detection.